PEMANFAATAN SUKUN SEBAGAI BAHAN ALTERNATIF PEMBUATAN MAYONAISE NABATI DENGAN PENAMBAHAN RPO (MINYAK SAWIT MERAH) SEBAGAI SUMBER BETA KAROTEN - Nur Wahyuni; Titik Sulistyani (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2021)
Breadfruit mayonnaise is a semi-solid emulsion with the addition of red palm oil (RPO) and salad oil. Breadfruit is a functional food with high nutritional content so that it has the potential to be used as an alternative food. There is a high carotenoid content in red palm oil as a source of provitamin A. This type of research is an experiment of RPO and salad oil to make breadfruit mayonnaise with four comparative variations, namely X1 samples (5gr:45gr); X2 (10gr:40gr); X3 (15r:35gr); and X4 (25gr:25gr). The mayonnaise gratitude test conducted on 30 Yogyakarta Academy of Social Welfare